VOLEYBOLDÍ OQÍTÍW METODIKASÍNDA ZAMANAGÓY PEDAGOGIKALÍQ TEXNOLOGIYALAR - Utegenov, Marat Bisenbaevich (SCIENCE and SOCIETY, 2026)
The article highlights the theoretical and practical foundations of using modern pedagogical technologies in teaching volleyball as a discipline. The article analyzes the role of interactive methods, information and communication technologies, and innovative pedagogical approaches in the effective organization of volleyball training. The significance of new pedagogical technologies in the physical development of students, the formation of motor skills, and the enhancement of their interest in sports is also scientifically substantiated.